Exploring the Lived Experiences of the Ilocos Sur Polytechnic State College Students in the New Learning Environment - Orpia, Cherie (Journal of Public Representative and Society Provision, 2021)
This study aims to explore the lived experiences of Ilocos Sur Polytechnic State College students in facing the new learning environment triggered by the COVID-19 pandemic. This study used a qualitative method with a phenomenological approach to understand the challenges faced by students during online learning and the coping strategies they used. Data were collected through semi-structured interviews with ten students enrolled in the Bachelor of Hospitality Management program. Thematic analysis results showed that students faced significant challenges such as limited high-speed internet access, mental health issues, and poor time management. On the other hand, students developed several coping strategies such as self-explanation, technological skill enhancement, and self-realization to overcome the difficulties faced. This study provides important insights into the impact of the pandemic on students' learning process and the importance of coping strategies in the new learning environment.